STRATEGY OF PRESERVATION AND DEVELOPMENT OF IKAT WOVEN FABRIC IDUP PANAK IN TENGANAN PEGRINGSINGAN VILLAGE - Utami, Ni Luh Ayu Pradnyani; Sukawati, Tjokorda Gde Abinanda; Karuni, Ni Kadek (Journal of Aesthetics, Design, and Art Management, 2024)
Purpose: This research aims to analyze the preservation and development strategies of idup panak ikat woven fabric in Tenganan Pegringsingan Village, Bali, focusing on the application of the concepts of upcycling and revivalism. The research also explores how these practices can contribute to the cultural preservation and economic sustainability of the local community. Research Methods: This research used a qualitative approach with a case study of the Tenganan Pegringsingan Village community. Data were collected through in-depth interviews with local weavers, direct observation of the production process, and literature studies related to weaving techniques, upcycling, and revivalism. Data were analyzed descriptively and interpretively to identify key themes. Findings: The results showed that the Tenganan Pegringsingan community has successfully adopted the concept of upcycling by utilizing leftover yarn from the production of gringsing cloth to create “idup panak” ikat woven fabric. In addition, the revivalism strategy is applied by integrating traditional motifs into contemporary designs. The combination of these two approaches not only maintains the cultural value but also increases the attractiveness of the product in the modern market. Implications: This research makes an important contribution to the understanding of how cultural heritage can be adapted to meet the demands of the contemporary market. The application of the concepts of upcycling and revivalism to the idup panak ikat woven fabric can serve as a model for other artisan communities in developing sustainable creative products.